Buildings and Structures under Extreme Loads - Bedon, Chiara; Stochino, Flavio; Honfi, Daniel (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
Exceptional loads on buildings and structures may have different causes, including high-strain dynamic effects due to natural hazards, man-made attacks, and accidents, as well as extreme operational conditions (severe temperature variations, humidity, etc.). All of these aspects can be critical for specific structural typologies and/or materials that are particularly sensitive to external conditions. In this regard, dedicated and refined methods are required for their design, analysis, and maintenance under the expected lifetime. There are major challenges related to the structural typology and material properties with respect to the key features of the imposed design load. Further issues can be derived from the need for risk mitigation or retrofit of existing structures as well as from the optimal and safe design of innovative materials/systems. Finally, in some cases, no appropriate design recommendations are available and, thus, experimental investigations can have a key role within the overall process. In this Special Issue, original research studies, review papers, and experimental and/or numerical investigations are presented for the structural performance assessment of buildings and structures under various extreme conditions that are of interest for design.